Gigi Sehat Tahun 2000 dan Tinjauan Profil Kesehatan Gigi 1995 - Christina Maria Kristanti; Yuyus Rusiawati (Journal of Dentistry Indonesia, 2015)
Reviewed indicators of Nationa Household Health Survey (NHHS) 1995 were done to know whether the target of dental health for all by the year 2000 which was the program goals has been achieved. The indicators reviewed were index DMF-T, prevalence of dental caries, percent people with with complete teeth. Index DMF-T is a total number of D-T (decayed teeth) score, M-F (missing teeth) score and F-T (filled teeth) score that shows level of seriousness of dental damage caused by dental caries/cavity. The findings showed that indicator “DMF-T index among children aged 12 years” was low (2.21) and achieved the target. But it is not a positive one finding that the score was dominated by D_T score which have not been took up yet, and the high prevalence of population with dental caries experience which was covered 77% of children aged 12 years. Indicator “population aged 18 years that retain all their teeth” is not a sharp one because it is only show the retaining of teeth without knowing the conditions of teeth, loss, or caries. Target year 2000 that was “ 75% population aged 35-44 years have a minimum of 20 functional teeth” can not been achieved. Indicator of “children aged 5 years with caries free” was not collected by SKRT 1995, but it is needed to monitor the program prevention. Indicator ‘population with deep pocket” is important to know the damage of teeth that caused by periodontal diseases. It is recommended to have a comprehensive services which consist of promotion, protection, early diagnosis and prompt treatment. Indicator ‘prevalence of caries” on a couple of age groups is needed, and also indicator of “children aged 5 years with caries free” and “population with deep pocket” specifically on age 35-44 years and 65+ years.